2007
DOI: 10.1088/0960-1317/17/4/014
|View full text |Cite
|
Sign up to set email alerts
|

Application of PECVD SiC in glass micromachining

Abstract: In this paper, we present an application of SiC for Pyrex glass micromachining in the MEMS fabrication process. SiC has very high etch resistance in most acid and alkaline solutions due to its chemical inertness. The PECVD (plasma-enhanced chemical vapor deposition) process allows deposition of SiC at a low temperature (200–400 °C), which makes SiC have better compatibility with IC fabrication. The PECVD SiC film was characterized and the process was optimized accordingly. An annealing process was developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
1
12
0
2
Order By: Relevance
“…Previous work [16][17][18] reported that amorphous SiC as mask is almost an inert material in HF solution for wet etching of glass [18,19]. Moreover, its hydrophobic surface avoids an easy penetration of the solution through the small defects of the masking layer.…”
Section: Amorphous Sicmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work [16][17][18] reported that amorphous SiC as mask is almost an inert material in HF solution for wet etching of glass [18,19]. Moreover, its hydrophobic surface avoids an easy penetration of the solution through the small defects of the masking layer.…”
Section: Amorphous Sicmentioning
confidence: 99%
“…Another commonly used mask material for glass etching is silicon-LPCVD (polysilicon) [12], PECVD (amorphous silicon) [11,13,14], or even bulk silicon [15]. Silicon carbide was also tested as a masking layer for micropatterning of glass in [16][17][18] for its small etch rate around 10 nm/h [19,20] in highly concentrated HF solution. The maximum reported deep etching through 1 mm-thick Pyrex glass wafer [14] uses a multiple layer mask of low stress amorphous silicon/silicon carbide/photoresist.…”
Section: Introductionmentioning
confidence: 99%
“…If the masking layer presents a hydrophilic surface, the etching solution will easily penetrate through this crack and generate a pinhole. Many masking materials for wet etching of glass have been reported in the literature, including photoresist, 52 amorphous Si deposited at low (200 C) 53 or high temperatures (570 C), 54 LPCVD polysilicon, 55,56 Cr/Au, 57 Cr/photoresist, 58 bulk Si, 59 amorphous SiC/ PECVD, 60 Ag, 61 Mo, 62 and Ti. 63 A detailed analysis of masking materials used in wet etching of glass is presented in Ref.…”
Section: Wet Etchingmentioning
confidence: 99%
“…10,12,14 The planar surface necessary to use a-SiC as a hard mask in these applications can be potentially achieved using chemical mechanical planarization (CMP).…”
mentioning
confidence: 99%
“…These characteristics make them suitable as etch masking layers during advanced semiconductor, solar cell and micro-electro mechanical system (MEMS) fabrication. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Examples of these applications include deep etching of glass or silicon, protection of low-K dielectric films, as a stop layer in STI CMP, etc. 10,12,14 The planar surface necessary to use a-SiC as a hard mask in these applications can be potentially achieved using chemical mechanical planarization (CMP). 14 Since, the a-SiC hard mask layers typically protect an underlying dielectric material, generally SiO 2 , the CMP polish process must be selective to it.…”
mentioning
confidence: 99%